The antioxidant and anti-elastase activities of tamarillo fruit extract (Solanum betaceum) - Fioni, Fioni; Liena, Liena; Siregar, Lusyana; Girsang, Ermi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Skin aging is a complex process characterized by structural and functional loss of skin tissue. Aging is triggered by reactive oxidative stress (ROS), which activates enzymes involved in the aging process, such as elastase. Tamarillo is one of the natural plants that has various chemical compounds that have the potential to be antioxidants and anti-aging. The objective was to examine the antioxidant and antiaging activity of Tamarillo Fruit Extract (TFE). The H2O2 scavenging assay and anti-elastase assay were used. The result shows that TFE has a high antioxidant activity, as evaluated by H2O2 scavenging activity. The highest scavenging activity was found in a TFE concentration of 500 µg/mL (72.96%). Meanwhile, TFE shows its highest anti-elastase activity at a concentration of 66.67 µg/mL (32.33%). TFE's activity in both antioxidant and antiaging assays was concentration-dependent. The IC50 of the H2O2 assay was 278.20 µg/mL, and the IC50 of the anti-elastase assay was 110.67 µg/mL. Therefore, TFE shows its antioxidant and antiaging activities and has the potential to be used in further studies, both in vivo and clinical studies.